RE-COVERY DVT/PE: Rationale and design of a prospective observational study of acute venous thromboembolism with a focus on dabigatran etexilate (Thrombosis and Haemostasis, 2017)
The therapeutic management of venous thromboembolism (VTE) is rapidly evolving. Following the positive results of pivotal large-scale randomised trials, the non-vitamin K antagonist oral anticoagulants (NOACs) represent an important alternative to standard anticoagulation. In phase III studies, dabigatran was as effective as, and significantly safer than warfarin. Additional information on real-world data of dabigatran is now warranted. RE-COVERY DVT/PE is a multi-centre, international, observational (i. e. non-interventional) study enrolling patients with acute DVT and/or PE within 30 days after objective diagnosis. The study is designed with two phases. Phase 1 has a cross-sectional design, enrolling approximately 6000 patients independently of treatment choice, with the aim of providing a contemporary picture of the management of VTE worldwide. Phase 2 has a prospective cohort design, with follow-up of one year, enrolling 8000 patients treated with dabigatran or vitamin K antagonists (VKAs) with the aim of comparing their safety, defined by the occurrence of major bleeding, and effectiveness, defined by the occurrence of symptomatic recurrent VTE. RE-COVERY DVT/PE will complement both the results of other observational studies in this field and the results of phase III studies with dabigatran, in particular by assessing its clinical benefit in various patient subgroups treated in routine clinical practice.
Keywords: Deep-vein thrombosis; pulmonary embolism; dabigatran; anticoagulation